(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Total of 60 (30 each) of two distinct strains of adult guinea fowls (Pearl and Belgy) comprising of 6 males and 24 females for each strain were used to compare and assess the egg quality of two guinea fowl strains. The external egg quality traits measured were egg weight, egg length, egg width, shell weight, shell thickness and egg shape index while the internal egg quality traits measured were yolk weight, yolk height, yolk diameter, yolk index albumen weight, albumen height, albumen diameter and albumen index. Data obtained were analyzed using General Linear Model Procedure of SAS. Means within the traits were compared using Duncan’s Multiple Range Test. Belgy strain had higher values for external egg quality traits for egg weight, egg length, egg width, shell weight and egg shape index were found respectively as 57.38±0.71g, 52.20±0.04mm, 40.10±0.04mm, 6.41±0.09g and 76.14±0.39% and internal egg quality traits for yolk weight, yolk height, yolk diameter, yolk index albumen weight, albumen height, albumen diameter and albumen index were found as 14.83±0.36g, 1.58±0.03mm, 43.35±1.92%, 35.75±0.61g, 6.50±0.01mm, 6.48±0.07mm and 9.95±0.19% than Pearl strain for all the egg quality traits. The significant difference observed for these traits between Belgy and Pearl suggests at least some degree of genetic variability. Belgy strain should be used in place of Pearl strain for improvement of egg quality of guinea fowl strains